Dispute between the family of the very seriously ill patient and the doctors. (November 2020) - Samuels, Alec
Abstract: The decided cases on disputes between the doctor and the family of the patient. A consideration of the relevant factors, such as the prognosis, the quality of life, the wishes of the patient, the tolerability of the patient, futility, dignity. Discussion of possible alternatives, such as wait and see. Ultimately the best interests of the patient must prevail.